Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1097/bpo.0000000000000391
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Deep Vein Thrombosis and Pulmonary Embolism in the Elective Pediatric Orthopaedic Patient

Abstract: Background Although venous thromboembolism has been well studied in the pediatric trauma population, rates of VTE associated with elective pediatric orthopaedic procedures have not been addressed in current literature. The purpose of this retrospective study was to identify the incidence of venous thromboembolism (VTE) in the elective pediatric orthopaedic surgical population and delineate subsets of this population at greatest risk. This study may provide valuable data to begin the process of resolving the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 35 publications
1
63
2
Order By: Relevance
“…The first of these was obesity, which has been demonstrated to be a risk factor for VTE in both adult and pediatric populations. 12,38 LE fracture and osteotomy procedures were also expected to be a risk for VTE based on previous literature, but no association was identified in this analysis. 38 Older age did not emerge as a risk factor despite previous studies implicating older age as a risk factor for VTE in children.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…The first of these was obesity, which has been demonstrated to be a risk factor for VTE in both adult and pediatric populations. 12,38 LE fracture and osteotomy procedures were also expected to be a risk for VTE based on previous literature, but no association was identified in this analysis. 38 Older age did not emerge as a risk factor despite previous studies implicating older age as a risk factor for VTE in children.…”
Section: Discussionmentioning
confidence: 65%
“…In a study of the pediatric orthopaedic population, Georgopoulos et al 12 reported that the incidence of VTE in 1 in 1,000 patients differs greatly from the adult orthopaedic population and is nearly double the incidence reported in previous pediatric orthopaedic retrospective studies. However, the authors excluded pediatric orthopaedic patients with procedures or diagnoses related to trauma, infection, malignancy, or coagulopathies as well as patients admitted through the emergency department or whose orthopaedic procedure was not performed on the admission date, potentially contributing to differences in VTE rates between studies.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…A retrospective study examining the risk of VTE in 171 sarcoma patients undergoing surgery included pediatric patients and reported an overall VTE rate of 4.1% . In comparison, another retrospective study that specifically excluded patients with malignancy found the overall incidence of pediatric VTE in elective orthopedic surgery to be only 0.06% . Although a direct comparison is not possible, these study results do suggest that surgery is an additional risk factor for VTE formation.…”
Section: Selection Of Patientsmentioning
confidence: 86%